Upaya Peningkatan Sikap Toleransi Melalui Media Powtoon Dalam Pembelajaran IPS Tentang Bentuk Keragaman Budaya Siswa Kelas IV SDN Dalung 1 - Nabila Agnesta Nur; Encep Supriatna (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is motivated by observations showing that tolerance is not practiced in elementary schools. The purpose of this study was to describe the process of learning tolerance through Powtoon media in social learning and to find out the results of increasing tolerance with the help of Powtoon media in social learning. The approach used in this research is a qualitative approach using classroom action research methods. Data analysis methods include observation, interviews and documentation. Researchers conducted data analysis to find out the results of the data collection techniques used. Data analysis uses four functions, namely data collection, data presentation, data reduction and inference. On Action Research in the Pre-Cycle, Cycle I and Cycle II which includes action planning, implementation, action observation and reflection. Research results found in psychology, ie. the results of observing student evaluations carried out in the pre-cycle, the researcher obtained a result of 5.92 or 14.81%, in Cycle 1 the results of student evaluation observations were obtained. result 9.96. namely 44.44%, then the results of the observation evaluation of students who completed Cycle II researchers obtained a score of 3.18 with an average of 11.96, namely 77.77%. Therefore, the researcher concluded that powtoon media can increase students' tolerance for several forms of cultural diversity in Social Studies IV at SDN Dalung 1.